Association between meeting 24-h movement guidelines and health in children and adolescents aged 5–17 years: a systematic review and meta-analysis - Zhao, HanHua; Wu, Na; Haapala, Eero A.; Gao, Ying (Frontiers in Public Health, 2024)
24-hour movement behaviors have significant implications for physical and mental health throughout one's lifespan. Consistent with movement behaviors, several countries have formulated and published 24-hour movement guidelines. This review summarized the studies related to 24-hour movement guidelines among children and adolescents from eight databases (MEDLINE, EMBASE, PubMed, Web of Science, CINAHL, and SPORTDiscus). 61 studies that discussed compliance with 24-hour movement guidelines, the adherence rate is very low (7.1%), with boys exceeding girls, children surpassing adolescents, and regional differences. 39 studies examined the associations between 24-hour movement guidelines and health indicators. Findings indicated that meeting all three guidelines was favorably associated with adiposity, cardiometabolic health, mental and social health, physical fitness, health-related quality of life, academic achievement, cognitive development, perceived health, dietary patterns, and myopia. Future research should utilize longitudinal and experimental designs to enhance our understanding of the association between 24-hour movement guidelines and health indicators, thereby aiding the formulation and refinement of such guidelines.